The binding of tyrosinyl-5'-AMP to tyrosyl-tRNA synthetase (E.coli). - Grosse, F (1979)
The binding between tyrosyl-tRNA synthetase (E.coli) and the alkylanalogue of the aminoacyladenylate, tyrosinyl-5'-AMP, has been investigated by fluorescence titrations and rapid mixing experiments. Tyrosyl-tRNA synthetase has two equivalent and independent binding sites for tyrosinyl-5'-AMP. The intrinsic binding constant is 4 x 10(7)M-1. The binding sites for tRNATyr and tyrosinyl-5'-AMP are independent of each other, the anticooperative mode of tRNA binding being preserved in the presence of tyrosinyl-5-AMP.